THE EFFECT OF WORKING CAPITAL ON COMPANY PROFITABILITY - Muh. Farhan; Goso Goso; H. Halim Palatte (SEAN Institute, 2023)
CV. Tirta Rumaju is a bottled drinking water company located in Rumaju Village, Bajo sub-district, South Sulawesi. This company made a new breakthrough in the bottled drinking water industry in Indonesia by producing bottled drinking water containing high oxygen levels with a tough brand. Oxygen is a water-forming element together with hydrogen (H20). Oxygen (02) is a compound that can affect the freshness level of water. The research method used is a quantitative research method. Quantitative research is research that involves and processes numbers with the help of statistical tools to test the hypothesis. This research is quantitative, namely research in the form of financial statements of the company Cv. Tirta Rumaju Rumaju Village, Bajo District, Sulawesi. Based on the results of research on working capital on profitability at CV. Tirta Rumaju Rumaju Village, Bajo District, South Sulawesi can be drawn the following conclusions: 1). Based on the results of a simple linear regression analysis, working capital (X) has a positive and insignificant effect on profitability (Y), where every one percent increase increases profitability by 0.169. Then the opportunity to get the maximum profit will be even higher. 2). The magnitude of the contribution or influence of working capital on profitability is 0.177 which means the effect of working capital on profitability is 17.7% and the remaining 82.3% is influenced by other factors not examined. 3). Based on the results of the t-test that has been done, it can be seen that t count ≤ t table, namely 0.804 ≤ 2.183. so the hypothesis is rejected, where it can be concluded that working capital has a positive and not significant effect on profitability at CV. Tirta Rumaju Rumaju Village, Bajo District, South Sulawesi.